Analisis Niat Penggunaan E-wallet Untuk Transaksi Pembayaran Oleh Mahasiswa - Erlinda Nur Khasanah; Sriniyati Sriniyati (ITB AAS INDONESIA, 2024)
The purpose of this study was to examine the effect of effort expectancy, behaviour, price value, and trust towards e-wallet’s usage continuance intention. The data used in this research was primary data collected by distributing questionnaires to students at Vocational Colleges in Special Region of Yogyakarta (DIY). The samples consisted of 92 samples. To test the hypotheses, this study used multiple regression analysis through the SPSS version 26 program. The results of this study indicated that performance expectancy, behaviour, and trust had a positive and significant effects on e-wallet’s usage continuance intention. Meanwhile, price value had no effect on e-wallet’s usage continuance intention.